Analysis of Early Reading and Writing Skills of Grade II Students at SDN Pendem 01 - Sofi, Cintami Nuryawati; Mukhlishina, Innany (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Early reading and writing skills are the main basis for the development of students' literacy in elementary school. However, observation results show that many students in the lower grades still have difficulty recognizing letters, pronouncing sounds, and writing with good neatness and readability. This study aims to analyze the initial reading and writing ability of second grade students of SDN Pendem 01 and identify the factors that affect it. The study used a descriptive qualitative method with data collection techniques through observation, interviews, and documentation of teachers and 10 students who were selected purposively. The results of the study showed that most students were able to read and write simple words and sentences, but there were still difficulties in distinguishing similar letters (b–d, p–q), understanding the content of the reading, and maintaining the proportion of writing. The main causative factors include limited exercise at home, differences in cognitive and fine motor skills, and learning methods that are still mechanical. Teachers try to overcome these obstacles through the use of letter card media, phonetic exercises, and interesting contextual writing activities. These findings confirm that reading and writing develop in parallel and reinforce each other, therefore, continuous collaboration between teachers and parents is needed in stimulating students' basic literacy in a systematic and fun manner.